An Audit Checklist for Mental Health Support Systems in Educational Institutions - Ramdas Ransing; Liza Choudhury; Vaibhav Puranik; Tapan Kumar Kalita; Sourabh Saha; Mala Das (Annals of Indian Psychiatry, 2026)
Abstract Background: Supreme Court of India (SCI) mandated 15-point guidelines to address the systemic gaps for mental health support in educational institutions. In our experience, the implementation of these guidelines is difficult due to the absence of an audit checklist, which is essential for systematically verifying compliance with predefined standards and criteria/requirements through objective evidence. To address this real-world challenge, this study was aimed to develop a structured and objective audit checklist to assess the mental health systems in educational institutions. Methodology: A multi-step approach was adopted to develop the audit checklist, including (i) a review of national/international guidelines including SCI, (ii) identification of key domains, and (iii) development of measurable indicators based on objective criteria and document-based verification, in consultation with stakeholders (e.g., principals, program officers, and mental health professionals). Then, checklist was pretested using cognitive interviewing with educational institutions ( n = 10) to assess clarity, interpretability, and feasibility of items. Results: Thirteen core domains and two context-specific domains were identified through a review of SCI, national, and international guidelines. Following stakeholder consultation and iterative refinement, the final audit checklist was developed based on these domains, with measurable indicators, objective scoring criteria, and document-based verification methods. Pretesting with educational institutions ( n = 10) demonstrated that the items were generally well understood by intended users and also indicated that the checklist was feasible to administer, acceptable to users, and appropriate for real-world settings. Conclusion: The developed audit checklist provides a practical and scalable approach for assessing institutional mental health systems aligned with SCI guidelines. It has the potential to support standardization, strengthen monitoring, and improve mental health systems in educational institutes. However, the checklist requires further validation as the part of a large multicentric study.